Characterization of Bilimbi (Averrhoa bilimbi) and its potential agro-industrial processes - Rosado Landazuri, Elian Joel; Meza Cisneros, Josueth Alfonso (Tierra Infinita, 2024)
The bilimbi (Averrhoa bilimbi), a tropical fruit cultivated in several countries, including Ecuador, thrives in warm and humid coastal and eastern regions, requiring temperatures between 20 and 30 degrees Celsius and an annual precipitation of at least 1500 mm. Well-drained soils rich in organic matter with a pH between 5 and 6.5 are essential for optimal growth. In Ecuador, it is known as Grosella China, and while similar fruits such as carambola and Indian gooseberry exist, bilimbi has been used in Asian culinary and traditional medicine due to its sour and refreshing taste, although scientific evidence regarding its medicinal properties is limited. Its versatility is reflected in agro-industrial applications, including the production of jams, sauces, vinegars, bakery, and dairy products, harnessing its antioxidant and antimicrobial properties. It also finds use in cosmetics and natural dyes due to its high vitamin C and oxalic acid content. Furthermore, its adaptability to various soil and climate conditions enhances its potential as an agro-industrial crop. Current research focuses on evaluating its feasibility in production processes and industrial applications, such as wine, vinegar, and preserves production, highlighting the growing interest in harnessing its potential in different industrial sectors